Strategi Pengembangan Pemanfaatan Ruang Rilayah Tanjung Pallette Dalam Menunjang Fungsinya Sebagai Daerah Wisata di Dabupaten Bone - Dzulfadhli Dzulfadhli; Rudi Latief; Ilham Yahya (Journal of Urban Planning Studies, 2021)
This study aims to determine the strategy of developing and utilizing the space of the Tanjung Pallette area to support its function as a tourist destination, especially in Bone regency. The analysis technique used is descriptive analysis and SWOT analysis. Descriptive analysis is used to determine the conditions in the field in Tanjung Palette clearly accompanied by a comparison. SWOT analysis is used to determine the strategy of Tanjung Palette in its development as a tourist destination (DTW). The results of this study indicate that the tourism sector, in this case Tanjung Palette tourism, has an important role in regional development in Bone Regency. For the development strategy of Tanjung Palette, there must be a formulation of government policies to support the development of the Tanjung Palette tourism sector in supporting its function as a tourist area